Takotsubo Cardiomyopathy: A Brief Review - Hilman Zulkifli Amin; Lukman Zulkifli Amin; Ariel Pradipta (2020)
Takotsubo cardiomyopathy is a reversible cardiomyopathy with a unique morphological feature of the left ventricle characterized by an apical ballooning appearance known for approximately known 25 years. Catecholamine drive plays an essential role in the pathogenesis and pathophysiology of Takotsubo cardiomyopathy; hence, it is also called stress cardiomyopathy. Physical stress could also have an impact and leads to a greater variety of characteristics in Takotsubo cardiomyopathy. Supportive and symptomatic medication remains the mainstay therapy with priority to improving the function of the left ventricle for several days and full recovery in 3-4 weeks. Due to its similarity with myocardial infarction, Takotsubo cardiomyopathy requires careful diagnosis and management for the best possible outcome.